1989
DOI: 10.1111/j.1476-5381.1989.tb16863.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophages and eicosanoids but not neutrophils, mediate bronchoconstriction induced by FMLP in the guinea‐pig

Abstract: 1 N-formyl-methionyl-leucyl-phenylalanine (FMLP), when administered by aerosol to guineapigs, induced a dose-dependent bronchoconstriction (BC) with no overt effect on platelet and leukocyte blood counts. Repeated administration of FMLP by aerosol was followed by desensitization. 2 Electron microscopy studies showed that administration of FMLP by aerosol is accompanied by alveolar macrophage activation, accumulation and aggregation in the alveolar lumens. Nondegranulated eosinophils were observed in the lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…This pretreatment, however, significantly reduced the release of TxB2 induced by aerosolized arachidonic acid, and has been reported to suppress the bronchoconstriction induced by aerosolized FMLP in the guinea-pig. Indeed, Boukili et al (1989) have demonstrated that indomethacin administered by aerosol to anaesthetized guinea-pigs significantly reduced the bronchoconstriction induced by both intravenous and aerosol administration of FMLP and abrogated that evoked by intravenous injection of arachidonic acid, suggesting a predominant cyclooxygenase-dependent component in these experiments. Under our experimental conditions, aerosol administration of indomethacin (100mgml-1, for 20min) suppressed the in vivo bronchoconstriction evoked by intravenous injection of arachidonic acid (0.5mgkg-'; Pons et al, unpublished results). Interestingly, although pretreatment of the animals or addition of indomethacin to the perfusion medium significantly decreased TxB2 formation induced in vitro by arachidonic acid by more than 65%, minimal effect of this drug on the increase in PIP was noted.…”
Section: Discussionmentioning
confidence: 76%
“…This pretreatment, however, significantly reduced the release of TxB2 induced by aerosolized arachidonic acid, and has been reported to suppress the bronchoconstriction induced by aerosolized FMLP in the guinea-pig. Indeed, Boukili et al (1989) have demonstrated that indomethacin administered by aerosol to anaesthetized guinea-pigs significantly reduced the bronchoconstriction induced by both intravenous and aerosol administration of FMLP and abrogated that evoked by intravenous injection of arachidonic acid, suggesting a predominant cyclooxygenase-dependent component in these experiments. Under our experimental conditions, aerosol administration of indomethacin (100mgml-1, for 20min) suppressed the in vivo bronchoconstriction evoked by intravenous injection of arachidonic acid (0.5mgkg-'; Pons et al, unpublished results). Interestingly, although pretreatment of the animals or addition of indomethacin to the perfusion medium significantly decreased TxB2 formation induced in vitro by arachidonic acid by more than 65%, minimal effect of this drug on the increase in PIP was noted.…”
Section: Discussionmentioning
confidence: 76%
“…We demonstrate that different pathways are involved with the transduction of the signals generated by these agonists. The intravenous injection of fMLP or of PAF to guinea-pigs induced bronchoconstriction, a prolonged pulmonary sequestration of leucocytes and a transient sequestration of platelets, long lasting leucopenia and thrombocytopenia, increased capillary exchanges and a decrease of the lung blood volume, indicating pulmonary vasoconstric-40 50 60 tion Boukili et al, 1989). Imaizumi et al (1992) demonstrated that bronchoconstriction by intravenous fMLP in guinea-pigs is prevented by pertussis toxin, as is the Lt on PAF-induced lung case here for intra-tracheal fMLP (Kadiri et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…tion has previously been demonstrated only under in vitro conditions. Although fMLF-induced cross-desensitization in vitro has been well documented, [13][14][15][16][17] in most cases it has been reported that the administration of fMLF in vivo induces typical effects of chemoattractants on neutrophils, such as neutrophil infiltration into the airway induced by the inhalation of fMLF [22][23][24] and transient neutropenia induced by the intravenous administration of fMLF. 25,26 Among these studies, only Ley et al 25 reported the possibility of an inhibitory effect of fMLF on neutrophil migration towards chemoattractants.…”
Section: Discussionmentioning
confidence: 99%